Germs of local automorphisms of real analytic CR structures and analytic dependence on the k-jets - ZAITSEV, DMITRI (International Press, 1997)
The topic of the paper is the study of germs of local holomorphisms f between Cn and Cn ? such that f(M) M? and df(TcM) = TcM? for M Cn and M? Cn ? generic real-analytic CR submanifolds of arbitrary codimensions. It is proved that for M minimal and M? finitely nondegenerate, such germs depend analytically on their jets. As a corollary, an analytic structure on the set of all germs of this type is obtained.
PUBLISHED
Keywords: Pure & Applied Mathematics